MOLECULAR CHARACTERISATION OF POTATO GENOTYPES FOR LATE BLIGHT RESISTANCE - Sharma, Reena; Kaushik, S K; Bhardwaj, Vinay; Sharma, Sanjeev; Bhatt, A K; Singh, B P (Potato Journal, 2013)
A number of major resistance (R) genes for late blight resistance have been introgressed from wild relatives into cultivated potato through hybridization. Eleven such genes have been described from solanum demissum, a wild hexaploid species. Among these eight have been mapped so far. Further, four R-genes within this set have been cloned (R1, R2, R3a, R3b). In the present study, markers for R1, R2 and R3a genes were first validated in a set of 21 late blight differentials with known R-genes and later a collection of indigenous and exotic potato genotypes was screened using linked markers. On the basis of marker screening, 17 genotypes were identified with R1 gene, 18 genotypes were having R2 gene and 41 genotypes possessed R3a gene. Besides 17 genotypes had combinations of these genes. This population was phenotyped for late blight resistance by detached leaf method, revealing association between presence or absence of the marker and phenotypic late blight resistance or susceptibility. Genotypes identified in this study with R1, R2 and R3a genes are being used in Indian resistance breeding programme for pyramiding these genes in single potato host background through marker assisted selection which is expected to provide enhanced durable late blight resistance.